Television viewing habits and their influence on physical activity and childhood overweight - Gisele F. Dutra; Cristina C. Kaufmann; Alessandra D.B. Pretto; Elaine P. Albernaz (Elsevier, 2015)
Objectives: To assess the prevalence of television (TV) viewing habits and their association with childhood sedentary lifestyle and overweight in 8-year-old children, from a cohort in a city in Southern Brazil. Methods: A prospective cohort study with hospital screening of all births that occurred from September of 2002 to May of 2003. This study refers to a cross-sectional analysis of data collected during the cohort's follow-up conducted at 8 years of age. To evaluate the level of physical activity, a physical activity questionnaire for children and adolescents was used (PAQ-C), during the consultation at 8 years of age. Results: Of the 616 interviewed children, a prevalence of sedentary lifestyle > 70% was found, as well as the habit of watching TV for more than two hours a day in 60% of the sample, regardless of gender (p = 0.30), income (p = 0.57), or family socioeconomic level (p = 0.90). The daily time spent watching TV was inversely associated with physical activity (p < 0.05) and positively associated with excess weight (p < 0.01). Regarding physical activity, running was the most frequently practiced sports modality among the population. Conclusions: Considering the high prevalence of sedentary lifestyle and children who watch TV for an excessive period of time, it is necessary to motivate such individuals to perform interactive activities, as well as promote a more active lifestyle, by decreasing the time children spend in front of the TV. Resumo: Objetivos: Avaliar a prevalência do hábito de assistir televisão (TV) e sua relação com o sedentarismo infantil e o excesso de peso, em crianças aos oito anos de idade, pertencentes a uma coorte de uma cidade do Sul do Brasil. Métodos: Estudo de coorte prospectivo, com triagem hospitalar de todos os nascimentos ocorridos entre setembro de 2002 a maio de 2003. O presente estudo refere-se a uma análise transversal dos dados coletados no acompanhamento da coorte ocorrido aos 8 anos de idade. Para avaliar o nível de atividade física, um questionário de atividade física para crianças e adolescentes foi utilizado (PAQ-C), durante a visita aos oito anos de idade. Resultados: Nas 616 crianças entrevistadas, encontrou-se uma prevalência de sedentarismo superior a 70%, e o hábito de assistir TV por um período superior a 2 horas diárias em 60% da amostra, independente do gênero (p = 0,30), renda (p = 0,57) ou nível socioeconômico (p = 0,90). O tempo diário assistindo televisão associou-se inversamente à prática de atividade física (p < 0,05) e positivamente ao excesso de peso (p < 0,01). Com relação à atividade física, corrida foi a prática esportiva mais frequente na população. Conclusões: Diante da elevada prevalência de sedentarismo e de jovens que assistem TV por um período excessivo, faz-se necessário o estímulo a atividades interativas, bem como a promoção de um estilo de vida mais ativo, com a redução do tempo que jovens dispensam em frente à TV. Keywords: Children, Cohort studies, Physical activity, Sedentary lifestyle, Television, Palavras-chave: Crianças, Estudos de coorte, Atividade física, Sedentarismo, Televisão